Senior High School as Critical Pedagogy - Jr., Mario Y. Palbusa, (Asian Journal of Contemporary Education, 2021)
Given the tendencies of education to become oppressive in theory and practice, exploring the premises of critical pedagogy as an educational philosophy becomes timely and compelling. This study aims to describe the possibilities of intensifying the essential role of pedagogy in teaching-learning processes, thereby leading to the framing of a liberating curriculum. In this qualitative phenomenological study, stories from purposively selected Senior High School stakeholders were collected through interviews, survey, and observations. After careful analysis, it revealed that some of the existing pedagogical practices still adhered to the traditional approach that deterred education from its being a genuinely free act. Proofs were gleaned from the areas of instruction, assessment, and learning environment. It is recommended that by strengthening critical pedagogy, learners become agents of social change. Teachers should then also be curriculum reformers who could make learning not just relevant but also liberating, and hence, humanizing.